Pengaruh Motivasi dan Lingkungan Kerja terhadap Kinerja Karyawan pada Dinas Perkebunan Kabupaten Fakfak - Maria Wesso; Agustina Waromi; Fenska Mbaubedari (Global Leadership Organizational Research in Management, 2025)
The research entitled The Influence of Motivation and Work Environment on Employee Performance at the Fakfak Regency Plantation Service. The purpose of this study is to find out: 1) To find out employee perceptions about Motivation, work environment, and employee performance at the Fakfak Regency Plantation Service, 2) To find out the significance of the partial influence of Motivation and environment on employee performance Is work discipline employee performance at the Fakfak Regency Plantation Service, 3) To find out the significance of the simultaneous influence of motivation and work environment on employee performance at the Fakfak Regency Plantation Service. This research is a quantitative type that is structural in nature, namely looking for the relationship between motivation and work environment on employee performance at the Fakfak Regency Plantation Service. The sample used in this study was 50 employees. Data were collected using interview techniques, questionnaires and documentation and analyzed using descriptive and inferential statistics using the Smart PLS 3.8 application. The results of descriptive statistical analysis show that the employee performance variable is 79.91%, work motivation is 80.55%, work environment is 86.8% which is included in the good category. The results of the Inferential statistical test show that partially the Motivation variable has a significant effect on employee performance with a t value of 2,341 and a significance value of 0.024. then the decision is to accept the alternative hypothesis (Ha), partially the work environment variable has a significant effect on the employee performance variable with a t value of 3,694 with a significance value of 0.001, then the decision is to accept the alternative hypothesis (Ha). The results of the statistical test based on Anova calculations show a calculated F value of 39,120 with a significance value of 0.000. This significance value is smaller than the alpha level used, which is 5% or 0.05, so the 2 (two) independent variables in this study simultaneously have a positive and significant influence on employee performance. The coefficient of determination (R2) is 0.700%. This means that the work motivation and work environment variables contribute 70% to the variation in employee performance at the Fakfak Regency Plantation Service, while the remaining 30% is explained by other variables not included in this study. Based on the results of this study, it is recommended that employees at the Fakfak Regency Plantation Service need to improve their work motivation to excellent levels by implementing all leadership policies in carrying out their duties and responsibilities.